Reactogenicity and immunogenicity after a late second dose or a third dose of ChAdOx1 nCoV-19 in the UK: a substudy of two randomised controlled trials (COV001 and COV002) - Flaxman, A; Marchevsky, NG; Jenkin, D; Aboagye, J; Aley, PK; Angus, B; Belij-Rammerstorfer, S; Bibi, S; Bittaye, M; Cappuccini, F; Cicconi, P; Clutterbuck, EA; et al. (Elsevier, 2021)
Background COVID-19 vaccine supply shortages are causing concerns about compromised immunity in some countries as the interval between the first and second dose becomes longer. Conversely, countries with no supply constraints are considering administering a third dose. We assessed the persistence of immunogenicity after a single dose of ChAdOx1 nCoV-19 (AZD1222), immunity after an extended interval (44–45 weeks) between the first and second dose, and response to a third dose as a booster given 28–38 weeks after the second dose.